Highly Strained Nanoscale Bicyclophane Monolayers Entering the Third Dimension: A Combined Synthetic and Scanning Tunneling Microscopy Investigation. Issue 6 (7th January 2021) - Henzel, Sebastian; Becker, Steven; Hennen, Daniel; Keller, Tristan J.; Bahr, Joshua; Jester, Stefan‐S.; Höger, Sigurd
Abstract: Tetrabromo aromatics can be synthesized by the Fischer‐Zimmermann condensation of appropriate pyrylium salts with arylene dicarboxylic acid salts. Their cyclization by intramolecular Yamamoto coupling yields strained bicyclophanes with adjustable sizes and different intraannular bridges. All compounds adsorb at the solid/liquid interface on highly oriented pyrolytic graphite (HOPG) and are investigated by scanning tunneling microscopy (STM) with submolecular resolution. The observed two‐dimensional (2D) supramolecular nanopatterns depend only on the sizes and alkoxy periphery of the cyclophanes and are independent of the specific structures of the intraannular bridges. Since the central arylene moieties of the smaller species are oriented perpendicular to the planes of the bicyclophanes, their substituents protrude from the surface by up to 1.6 nm after adsorption. Therefore, these molecules are attractive platforms for addressing the volume phase above the graphite surface. Abstract : Rising above the surface : Bicyclophanes of different sizes with different central units have been synthesized, including species with central units pointing out of the ring plane. Scanning tunneling microscopic investigations of self‐assembled monolayers of these compounds at the solid/liquid interface on graphite provide submolecularly resolved insights into the nanopatterns formed. After adsorption the central units point along the surface normal and protrude by up to 1.6 nm into the volume phase.